Physical self-concept in Peruvian adolescent schoolchildren: Validity, reliability, and proposal of percentiles for its evaluation - Fuentes-Lopez, Jose; Vidal-Espinoza, Rubén; Limachi-Flores, Mary; Callata-Gallegos, Zaida; Quispe-Cruz, Henry; Gomez-Campos, Rossana; Cossio-Bolaños, Marco (Frontiers in Education, 2023)
The period of adolescence is characterized by marked changes relevant to adult life. The goals of this study were a) to analyze the psychometric properties of the physical self-concept questionnaire (PSC) in adolescents and b) to develop percentiles for evaluation by age and sex. A descriptive cross-sectional study was conducted in adolescents aged 11 to 17 years from an altitude region of Peru (3,812 m above sea level). The sample size was 1,263 schoolchildren (609 males and 654 females). The PSC was measured through the survey technique. The questionnaire proposed by Fox, Corbin (1989), composed of five dimensions (totaling 30 questions), was applied. Validity was assessed by means of confirmatory factor analysis (CFA) and reliability by means of internal consistency (Cronbach's alpha). Percentiles were calculated using the LMS method (lambda: skewness, median; M and S: coefficient of variation). In the CFA, factor loadings (communalities) were satisfactory for the model. Values ranged from (0.30 to 0.60), in addition, the Kaiser-Meyer-Olkin KMO sample adequacy test was 0.89, X2= 3401.086, (gl: 395, p< 0.00), CFI (0.898), RMSEA (0.078) and % variation 47%. The reliability values (Cronbach's alpha) per question evidenced values from r= 0.80 to 0.81 and the total scale r= 0.81. Percentiles were calculated: p3, p5, p10, p15, p25, p50, p75, p80, p85, p90, and p95. This study concludes that the psychometric properties of the PSC questionnaire applied to adolescents living in an altitude region of Peru were valid and reliable. The proposed percentiles can be used to categorize and monitor PSC by age and sex. These results suggest their use and application in the school system.